Analysis of saponin composition and comparison of the antioxidant activity of various parts of the quinoa plant (Chenopodium quinoa Willd.) - Lim, Jeong Gyu (Food Sci Nutr, 2019)
Quinoa plant is a valuable food crop because of its high nutritional and functional values. Total saponin content, sapogenins, polyphenol, and flavonoid contents and antioxidant activities were analyzed in various parts of quinoa plants, including sprout, seeds, bran, pericarp, leave, stem, and root. Quinoa seeds (QS) had significantly higher sapogenin content than quinoa stem (QT), quinoa leaves (QL), and quinoa roots (QR). Quinoa saponin was mainly composed of phytolaccagenic acid. Quinoa root (QR) had the highest amount of total saponin (13.39 g 100 g(−1)), followed by quinoa bran. The highest total phenolic content (30.96 mg GAE 100 g(−1)) and total flavonoid content (61.68 mg RE 100 g(−1)) were observed in quinoa root extract and 1‐month‐old sprout extract, respectively. Quinoa sprouts showed better antioxidant activity than fully grown parts of the quinoa plant. Overall, root and sprout had a higher antioxidant capacity compared to other parts of the quinoa plant, suggesting the potential use of quinoa root and sprout as a nutraceutical ingredient in the health food industry.